Study of Subclinical Coccidiosis in Small Ruminants from Sulaymaniyah Province/ Iraq - Shadan Abdullah (Basrah Journal of Veterinary Research)
Coccidiosis caused by Eimeria species, with great economic importance infecting numerous species including small ruminants. The current study aimed to determine the occurrence of Eimeria subclinical infection in Sulaymaniyah provinces, during March 2021 to February 2022. A total of 260 fecal samples (152 sheep and 108 goats) were collected from small ruminants’ farms belong to four regions. Fecal floatation technique was applied for examination of fecal samples. Coprological examination revealed that Eimeria spp. parasitized the intestine of 133 animals with infection rate of 51.15%. Both sheep and goats represented subclinical coccidiosis with infection rates of 52.63% and 49.07% respectively. Mixed infection with more than one Eimeria spp. was dominant and found in sheep 60.00% and goats 40.00%. However, infection by single species was revealed in sheep 58.62% and goats 39.66% goats. The frequency of subclinical coccidiosis was higher among animals in Bakrajo 53.85%, and lower in Qaradagh 46.67%. The impacts of age on prevalence rate revealed that small aged animals harbored the higher infection rates of 65.45% and 62.86% in lambs and kids respectively. The represented data find out higher incidence of coccidiosis during the wet seasons of the year 56.8%. In the present study different Eimeria species was recognized, 9 species from sheep and 5 species from goats. It has been conducted that coccidiosis was a moderately common intestinal pathogen among sheep and goats in the study area.